تحديد الشروط المثلى لاستخلاص المركبات الفينولية من بعض أصناف القمح القاسي السوري باستخدام منهجية سطوح الاستجابة. - جمل نورا (Latakia University Journal -Biological Sciences Series, 2016)
تمَّ تحديد الشروط المثلى لاستخلاص المركبات الفينولية من بعض أصناف القمح السوري القاسي (حوراني، دوما 1، بحوث 11) باستخدام منهجية سطوح الاستجابة؛إذْ تمَّ استخدام التصميم المركب المركزي للتحقق من تأثير ثلاثة متغيرات مستقلة هي تركيز المذيب، ودرجة حرارة الاستخلاص، وزمن الاستخلاص على عامل الاستجابة، وهو كمية المركبات الفينولية المستخلصة. اختيرت القيم الفعلية بناءً على نتائج التجارب الأولية، واختبرت المتغيرات المستقلة على ثلاثة مستويات. تمَّ توقع نتائج الاستجابة من خلال استخدام نموذج متعدد حدود من الدرجة الثانية. أظهر تحليل الانحدار أن 95-97%من الانحرافات قد فسرت من خلال النموذج. كانت الشروط المثلى لاستخلاص المركبات الفينولية تركيز المذيب 49.5%، ودرجة الحرارة 55.5مْ ، والزمن 42.5 د لأصناف القمح الثلاثة، وكانت القيم المتوقعة ضمن الشروط المثلى 0.976 مغ مكافئ حمض غاليك /غ وزن جاف للصنف الحوراني، و 0.947 مغ مكافئ حمض غاليك /غ وزن جاف للصنف دوما 1 و 1.316 مغ مكافئ حمض غاليك /غ وزن جاف للصنف بحوث11. تمَّ استخلاص المركبات الفينولية تحت الشروط المثالية المتوقعة للتحقق من صلاحية النموذج، وكانت النتائج 0.965±0.05 و 0.932±0.03 و 1.214 ± 0.06مغ مكافئ حمض غاليك /غ عينة جافة من أصناف القمح حوراني، دوما1، بحوث11على التوالي. لقد دل تطابق النتائج التجريبية مع القيم النظرية المتوقعة من خلال النموذج المستخدم على ملاءمة النموذج، ونجاح منهجية سطوح الاستجابة في تحديد الشروط المثلى للاستخلاص. The optimal conditions for the extraction of polyphenolic compounds from hard Syrian wheatvarieties (Hourani, Doma1,Bohoos11) were determined using response surface methodology. A Central Composite Design was used to investigate the effects of three independent variables, namely solvent concentration, extraction temperature and time on the response phenolic content. The independent variables were at three levels and their actual values selected on the basis of preliminary experimental results. A second-order polynomial model was used for predicting the response. Regression analysis showed that more than 95-97% of the variation was explained by the models. The optimal conditions for phenolic compounds extraction were found to be acetone concentration of 49.5 %v/v, extraction temperature of 55.5°C, extraction time of 42.5min, for wheat. Under the optimum conditions the corresponding predicted response values for polyphenolic compounds were 0.976 mg EGA forHourani, 0.947 mg EGA forDoma1 and 1.316 mg EGA for Bohoos11. The phenlics were extracted under optimum conditions to check the validity of model, and the experimental values were 0.969±0.05 ,0.932±0.03 and 1.214±0.06 mggalic acid equivalent /g dry weight from wheatvarieties (Hourani, Doma1,Bohoos11) respectively. The good agreement between predicted and ,experimental values indicated suitability of the model employed and the success of response surface methodology in optimizing the extraction conditions.